2023
DOI: 10.3390/app13074618
|View full text |Cite
|
Sign up to set email alerts
|

Improving Film Cooling Efficiency with Lobe-Shaped Cooling Holes: An Investigation with Large-Eddy Simulation

Abstract: Shaped cooling holes have received considerable attention in recent years due to their potential to improve heat transfer while minimizing pressure drop. In this study, the effects of lobe-shaped cooling holes on film cooling performance and turbulent flow characteristics are investigated using large-eddy simulation (LES). The LES approach was validated by comparing the calculated film cooling effectiveness with experimental data. The results show that well-designed lobe-shaped cooling holes can improve the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Yang et al [15] also studied film cooling patterns with upstream leakage and found that it benefited the film cooling from the film holes. Wang et al [16] numerically studied lobe-shaped holes using a large eddy simulation (LES) to track the flow field of film cooling. Zhao et al [17] used the response surface method to analyze the cooling characteristics of a stream-cooled blade.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [15] also studied film cooling patterns with upstream leakage and found that it benefited the film cooling from the film holes. Wang et al [16] numerically studied lobe-shaped holes using a large eddy simulation (LES) to track the flow field of film cooling. Zhao et al [17] used the response surface method to analyze the cooling characteristics of a stream-cooled blade.…”
Section: Introductionmentioning
confidence: 99%